Distribution of Cd, Cu, Pb, Zn, Al, Fe and Mn in dissolved and particulate phases of surface water in Songkla Lake System - Sorworraya Kongthong (2007)
Thesis (M.Sc., Analytical Chemistry)--Prince of Songkla University, 2007